Adequacies of lymphadenectomy range for gastric cancer according to the second and third/fourth Japanese gastric cancer treatment guidelines - Yo-Seok Cho; Hyuk-Joon Lee; Shin-Hoo Park; Tae-Han Kim; Hwi Nyeong Choe; Yun-Suhk Suh; Seong-Ho Kong; Han-Kwang Yang (Korean Journal of Clinical Oncology, 2017)
Purpose This study evaluated the adequacies of lymph node (LN) dissection according to the second version (determined by tumor location) or third/fourth version (determined by surgery extent) of the Japanese gastric cancer treatment guidelines. Methods Prospectively collected data of 3,948 gastric cancer patients who underwent gastrectomy were analyzed. The prevalence of LN metastasis and 5-year survival were analyzed according to tumor invasion depth and tumor location. In early gastric cancer (EGC), the frequency of LNs were evaluated. In advanced gastric cancer (AGC), the frequency of LN metastasis and the 5-year survival rate of patients with positive LN were evaluated. Results For lower-third EGC, the positive rates for the #1 and #4sb were 0.93% and 0%. For upper-third EGC, the positive rates for #4d, #5, #6, and #11p were 0.3%, 0%, 0.76%, and 1.22%. For lower-third AGC, the positive rates for #4sb and #14v were 2.48% and 7.64%, and the 5-year survival rates were 69.2% and 12.5%, respectively. For upper-third AGC, the positive rates for #5, #6, and #12a were 2.33%, 2.57%, and 2.03%, and the 5-year survival rates were 21.8%, 64.3%, and 0%, respectively. Conclusion According to our analysis, in EGC, LN dissection in second edition seems more suitable, however LN dissection in #11p would be mandatory in upper third EGC. In AGC, LN dissection in third/fourth edition seems more suitable in terms of frequency of LN metastasis and survival rate.